The Hypnoteaching Model in Teaching Javanese Speaking Skills to Generation Z High School Students - Eliza Naviana Damayanti; Suwardi Endraswara; Mulyana Mulyana (JOLLT Journal of Languages and Language Teaching, 2026)
This study is motivated by the declining ability of senior high school students, as representatives of Generation Z, to speak Javanese fluently and confidently due to globalization, the dominance of Indonesian and foreign languages, changing communication patterns, and the continued use of conventional teacher-centered learning methods. These conditions reduce students’ interest, participation, and confidence in using Javanese in both formal and informal communication. Therefore, innovative and interactive learning approaches are needed to support speaking competence while also contributing to regional language preservation. This study aims to analyze the implementation of the hypnoteaching model and its contribution to improving students’ Javanese speaking skills. The research employed a qualitative descriptive approach through literature review and document analysis using journal articles, educational documents, learning modules, and previous studies related to hypnoteaching and language learning as data sources. The data were analyzed using descriptive content analysis supported by thematic categorization and source triangulation to ensure validity. The findings indicate that hypnoteaching creates a supportive and psychologically conducive learning environment through stages such as intention and motivation, pacing, leading, positive words, rewards, modeling, and yelling. These stages contribute to improving students’ motivation, confidence, participation, speaking fluency, vocabulary accuracy, and willingness to communicate in Javanese. Furthermore, hypnoteaching is considered relevant to the interactive and experience-based learning characteristics of Generation Z students.